Oxidation mechanism of porous Zr2Fe used as a hydrogen getter. (January 2016) - Cohen, Dror; Nahmani, Moshe; Rafailov, Genadi; Attia, Smadar; Shamish, Zorik; Landau, Miron; Merchuk, Jose; Zeiri, Yehuda
Abstract: We determined the oxidation mechanism of porous ST-198, which mainly comprises Zr2 Fe. Oxidation kinetics depended on temperature, oxygen partial pressure, and oxidation extent. The passivation role of oxidation in hydrogen scavenging is probably due to the development of a surface oxide, independent of oxygen concentration. Zr2 Fe would be a superior hydrogen getter in oxygen-contaminated environments at high temperatures, as most oxygen will be consumed at the outer shell by mass transfer limitations, protecting the bulk of the getter for hydrogen scavenging. Highlights: Porous Zr2 Fe–O2 interactions are characterized in detail. Gettering efficiency at low temperature is hampered by oxide layer formation. Gettering is better at high temperatures as outer shell consumes maximum oxygen.